2002
DOI: 10.1679/aohc.65.323
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of the Communication Routes between the Epithelium and Lamina Propria Mucosae in the Human Esophagus.

Abstract: Morphological studies examined communication routes between the epithelium and lamina propria mucosae in the human esophagus, using a series of techniques including silver staining, immunohistochemistry, transmission electron microscopy, and scanning electron microscopy (SEM). For SEM, tissue blocks were treated with either osmium/ultrasonication or NaOH. Observations showed the esophageal papillae to be arranged regularly in a mostly longitudinal row. The reticular fibers, consisting of fibrils approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The present TEM study also confirmed that the esophageal Langerhans cells occurred within the epithelium [8]. On the other hand, immunohistochemical studies already illustrated that the human epidermal Langerhans cells were more positive for anti-S-100 protein, anti-MHC-Class II protein, anti-CD54, anti-CD80, anti-CD 86, and anti-CD40 [2,4]. In the present study, only anti-S-100 protein antibody was used to identify Langerhans cells.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The present TEM study also confirmed that the esophageal Langerhans cells occurred within the epithelium [8]. On the other hand, immunohistochemical studies already illustrated that the human epidermal Langerhans cells were more positive for anti-S-100 protein, anti-MHC-Class II protein, anti-CD54, anti-CD80, anti-CD 86, and anti-CD40 [2,4]. In the present study, only anti-S-100 protein antibody was used to identify Langerhans cells.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, transmission electron microscopic observation of the human esophagus demonstrated that Langerhans cells were also present within the stratified squamous epithelium [4]. The ultrastructure of Langerhans cells in the human esophagus was clearly identical with that of the human skin [8].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…EC is characterised by bidirectional and skipping LNM, mainly due to the longitudinally mucosal and submucosal lymphatic drainage [ 34 37 ]. Collateral vessels of lymph nodes were found because of the close topographical relationship between the afferent and efferent [ 38 ], which should be another reason for the skipping LNM.…”
Section: Discussionmentioning
confidence: 99%
“…Overnight incubation at 4°C with antibodies (Mab), diluted 100-fold with phosphate-buffered saline, was followed by incubation for 2 h at room temperature with 5-nm gold-labeled goat antibodies against rabbit lgG (British BioCell International, Cardiff, UK). Finally, sections were immersed in developer for 28 min in darkness and then counterstained with Nuclear Fast Red (Kernechtrot) [8]. Sections from case 2 were also fixed in 2.5% glutaraldehyde in 0.1 M cacodylate buffer (pH 7.4), postfixed in 1% osmic acid in the same buffer, dehydrated, and embedded in Epon 812 by standard methods.…”
Section: Methodsmentioning
confidence: 99%